Risk assessment of the occurrence of aflatoxin and fungi in peanuts and cashew nuts - Paula Kujbida; Patrícia Penido Maia; Ariadne Naama de Araújo; Leonardo Daniel Mendes; Mariana Lepri de Oliveira; Walicyranison Plinio Silva-Rocha; George Queiroz de Brito; Guilherme Maranhão Chaves; Isarita Martins
In the present study, the occurrence of fungi and aflatoxins (AFs) in peanut and cashew nut samples was investigated. Mycological analysis revealed the presence of fungi in 58.8% of samples, and assessment of AFs by chromatographic methods revealed that 52.9% were contaminated by AFs. AFB1 was the principal component in all AF-contaminated samples, with a mean level of 14.0, and 1.08 µg/kg in peanut and cashew nut, respectively. Eleven samples (32.4%) exceeded the total AF maximum level (4 μg/kg) and 8 samples (23.5%) exceeded the AFB1 (2 μg/kg) established by the European Commission. Our findings suggest that the incidence of AFs emphasizes the need for regular monitoring and a more stringent food safety system to control AFs at the lowest possible levels in peanuts and cashew nuts. The hypothetical dietary exposure suggests that the food products evaluated may significantly contribute to the overall human exposure.